MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK HOTEL KOTA KENDARI - Sarinah; Rasmin; Muhamat Arif Afandi; Febriansyah (Halu Oleo University, 2024)
This study aims to determine the modernization of the tax administration system in improving the compliance of hotel taxpayers in Kendari City. This research uses a qualitative methodology with a descriptive approach. Data was collected through in-depth interviews, document studies, and observations at the Kendari City Regional Revenue Agency, as well as hotel taxpayers in Kendari City. The results of this study indicate that the modernization of the tax administration system can improve hotel taxpayer compliance in Kendari City. This can be seen from the dimensions of the modernization of the tax administration system that are fulfilled, namely the administrative system has been based on communication and information technology, through the use of technology-based programs and online payments. Based on the modernization of the administrative system, is quite effective and efficient in increasing taxpayer compliance. The simplicity of using a modernized tax administration system is simple and understandable for taxpayers and can provide benefits for taxpayers in terms of reporting and monitoring taxation.